The prevalence of the MAOA µVNTR alleles and their relationship to childhood behaviour and personality within a South African cohort - Wessels, Stephan Herman (My University, 2020)
Historically, the X-linked monoamine oxidase A promoter variable number tandem repeat (MAOA µVNTR) low-activity (versus high-activity) alleles were thought to be associated with an increase in internalising and externalising behaviour problems in males. However, recent research has highlighted the importance of gene-environment (GxE) interactions as a modifier of this effect. Individuals with a low-activity allele, who were raised in a poor environment, show higher levels of behavioural problems, however, when these same individuals are in a supportive environment, they experience the lowest levels of behavioural problems compared to high-activity allele individuals. These crossover effects have been recently incorporated into a theory known as Environmental Sensitivity. This study aimed to genotype the MAOA µVNTR by PCR and gel electrophoresis within South African males (n = 543) and females (n = 593) of the Birth to Twenty Plus cohort. Genotypes were then correlated to historical cohort data on caregiver-rated childhood behaviour from the South African Child Assessment Schedule. When accounting for covariates (5-HTTLPR, gestational age, birth weight, maternal education, and household socio-economic status), linear regression analysis revealed that possessing a low-activity MAOA µVNTR allele was a predictor of internalising behaviour in males (p < 0.05) and females (p < 0.05) and externalising behaviour (p < 0.05) in males, but not sensory processing sensitivity (a psychological marker of environmental sensitivity) in either males (p > 0.1) or females (p > 0.1). Additionally, when maternal education was applied as an environmental modifier, a significant interaction (p < 0.01) revealed that males with a low-activity MAOA allele have externalising behavioural scores in direct proportion to maternal education levels. Moreover, males without a high-activity allele showed no change in externalising behaviour as a function of maternal education. When household socio-economic status was used as the environmental modifier in females, a significant interaction (p < 0.01) revealed a contrasting effect where low-activity allele carriers experienced an increase in internalising behaviour problems with an improved environment. However, high-activity allele carriers experience the opposite. These findings support the role of Environmental Sensitivity theory through GxE interaction models in predicting behavioural development.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2020